Orthodoxy in Dialogue with the Islam (1986-2012): a Comparative review of the Topics, Methods and Results of This Dialogue - Schon, Dietmar (Forum Theologicum Sardicense, 2025)
Dietmar Schon, Orthodoxy in Dialogue with the Islam (1986-2012): a Comparative Review of the Topics, Methods and Results of this Dialogue. The lecture is based on long-term research into the efforts of the Autocephalous Orthodox Churches to engage in dialogue with representatives of Islam. This commitment is demonstrated through various concepts and forms. The lecture focuses on two main approaches: 1) Bilateral interreligious dialogue, which involves only Orthodox Christians and Muslims; 2) Participation of Orthodox Churches in joint multilateral initiatives for dialogue, which include members of different Christian churches engaging in dialogue with Muslims, thereby aiming to display their Christian attitude.